# Calculus

posted by .

f(x)=5+(6/x)+(7/x^2), find f'(x).

I haven't done fractions without using the quotient rule im not so sure this would work with quotient rule what do i do?

• Calculus -

rewrite as:
f(x)=5 + 6*x^(-1) + 7*x^(-2)
The derivative of the first term is 0. For the derivative of the terms with x, multiply the exponent times the coeffecient of the term, the subtract 1 from the exponent.

## Similar Questions

1. ### Calculus

Let f(x)= 5x ------- x–2 are we supposed to use the quotient rule?
2. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
3. ### calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
4. ### Calculus

y= [(x-3)/(x^2+1)]^2 I know that I would use the product rule on the whole equation inside the brackets. But would i also do the quotient rule bc of the division?
5. ### Calculus

y= [(x-3)/(x^2+1)]^2 find the derivative. I know i would start off with the chain rule. but would i then continue on and use the quotient rule next?
6. ### Calculus-Math

Complete the table without using the Quotient Rule. Function y=2x^(7/2)/x Rewrite y= Differentiate y'= Simplify y' =
7. ### Calculus

Find f''(1/2) using f(x) = ln(1-x). f'(x) = 1/(1-x) * -1 = -1/(1-x) so then using quotient rule: f''(x) = ((-1*-1) - ((1-x)(0))) / (1-x)^2 f''(1/2) = 1/(1-(1/2))^(2) = 4 Is this correct?
8. ### Calculus

Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)-f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx [f(x)+g(x)]= …
9. ### Calculus

So, I have a homework question on The Quotient Rule (taking derivitives) and I would like to know if I did it right. Calculate: y=(1/sqrt(x))-(1/(5th root of x^3). My 1st step was to change the sqrt to x^1/2, and the 5th root to x^1/5+^3. …
10. ### Calculus

Quotient Rule: Use the limit definition of the derivative to prove that the quotient rule

More Similar Questions